Empty Migrant Rooms: An Anthropology of Absence through the Camera Lens - Pistrick, Eckehard; Bachmeier, Florian (Journal of Contemporary Archaeology, 2017)
The article explores "empty migrant rooms" in Central Albania and their photographic image as seen through an anthropology of absence. In which way can a dialogic work between ethnographer and photographer reveal the local meanings of such spaces as lieux de mémoire commenting on temporary absences and prospective presences? The authors explore the local terminology, the affective care and the social interaction generated by and around such rooms. It is argued that such spaces are not only fluctuating between the material and the immaterial, but are also characterized by emotional ambiguities. Their local relevance is referred to as "absence signifiers", as material substitutes for physical bodies of flesh and blood, as "memory boxes" of the immaterial. The article also discusses ethical questions which concern the very nature and the preservability of "migrant's traces".